PENGARUH BEBAN KERJA, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA (STUDI KASUS PADA PERAWAT RUANG RAWAT INAP RS PKU MUHAMMADIYAH SRUWENG) - Sofiatun Sofiatun; Much. Riyadus Solichin (Bajang Institute, 2023)
This study aims to examine the effect of: 1. Workload on the performance of nurses in the Inpatient Room of PKU Muhammadiyah Sruweng Hospital, 2. Motivation of Inpatient Nurses of PKU Muhammadiyah Sruweng Hospital 3. Job satisfaction on the performance of Inpatient Nurses of PKU Muhammadiyah Sruweng Hospital and 4. Workload, motivation and job satisfaction together on the performance of Nurses in the Inpatient Room of PKU Muhammadiyah Sruweng Hospital. The object of this research is the nurse in the inpatient room of PKU Muhammadiyah Sruweng Hospital with a sample size as many as 82 people who also became respondents in this study and data processed with statistic tool SPSS 22.0. The results of this study state that: 1. Workload has a significant influence on the performance of Inpatient Nurses at PKU Muhammadiyah Sruweng Hospital. 2. Motivation has a significant effect on the performance of Inpatient Nurses at PKU Muhammadiyah Sruweng Hospital 3. Job Satisfaction has a significant effect on the performance of Nurses in Inpatient Rooms at PKU Muhammadiyah Sruweng Hospital. 4. Workload, motivation, and job satisfaction have a significant influence on the performance of Inpatient Nurses at PKU Muhammadiyah Sruweng Hospital